2021
DOI: 10.1016/s2589-7500(20)30271-5
|View full text |Cite
|
Sign up to set email alerts
|

Referral for disease-related visual impairment using retinal photograph-based deep learning: a proof-of-concept, model development study

Abstract: Background In current approaches to vision screening in the community, a simple and efficient process is needed to identify individuals who should be referred to tertiary eye care centres for vision loss related to eye diseases. The emergence of deep learning technology offers new opportunities to revolutionise this clinical referral pathway. We aimed to assess the performance of a newly developed deep learning algorithm for detection of disease-related visual impairment. MethodsIn this proof-of-concept study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…These considerations include, the deployment site (ie, whether in rural community screening sites or primary care facilities), local regulatory requirements for implementation of health technology (which may require minimal levels of specificity and sensitivity to be achieved before rollout is granted), and availability of healthcare resources/ facilities for treatment (ie, communities with finite resources may opt for a more stringent threshold which would yield higher positive predictive value, to more strictly identify those which truly require treatment. 34 Fourth, it should be noted that the ground truth of referable pterygium was defined based on the presence of pterygium with >2.50 mm extension towards the cornea or with a base width of >5.00 mm, but did not take total area and fleshiness (ie, thickness) 20 of the pterygium into account. However, previous studies have indicated that horizontal extension along with the base width of the pterygium [23][24][25][26] have the greatest influence on corneal astigmatism and ocular aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…These considerations include, the deployment site (ie, whether in rural community screening sites or primary care facilities), local regulatory requirements for implementation of health technology (which may require minimal levels of specificity and sensitivity to be achieved before rollout is granted), and availability of healthcare resources/ facilities for treatment (ie, communities with finite resources may opt for a more stringent threshold which would yield higher positive predictive value, to more strictly identify those which truly require treatment. 34 Fourth, it should be noted that the ground truth of referable pterygium was defined based on the presence of pterygium with >2.50 mm extension towards the cornea or with a base width of >5.00 mm, but did not take total area and fleshiness (ie, thickness) 20 of the pterygium into account. However, previous studies have indicated that horizontal extension along with the base width of the pterygium [23][24][25][26] have the greatest influence on corneal astigmatism and ocular aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…The ResNet model did well in predicting the presence of any diseaserelated visual impairment, with an area under receiver operating characteristic curve (AUC) range varying from 86•6% (95% CI 83•4-89•7) to 93•6% (92•4-94•8) across the external validation datasets. 9 In external datasets, the AUC range for predicting mild diseaserelated visual impairment was 81•9% (77•2-86•6) to 92•5% (90•8-94•2) and for moderate diseaserelated visual impairment was 85•9% (81•8-90•1) to 93•5% (91•7-95•3). According to these AUC data, the model did quite well to identify disease-related visual impairment in the external datasets, indicating potential generalisability, which is a crucial element for widespread deployment and clinical utility.…”
mentioning
confidence: 91%
“…In April, 2018, the US Food and Drug Administration approved the first AI-based referral device for diabetic retinopathy. 8 In The Lancet Digital Health, Yih-Chung Tham and colleagues 9 report development of a single modality (fundus photograph) deep learning algorithm for the detection of disease-related visual impairment with the goal of creating a referral system in vision care. Following the recommendation of WHO, some high-income countries have implemented annual vision screening, especially for older populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…79In 2021, Yih-Chung Tham and coworkers proposed a new method for disease-related visual impairment diagnosis, employing retinal photograph-based deep learning 65. Patients affected by different major age-related eye diseases such as cataract, diabetic retinopathy, and maculopathy were included, and a deep CNN was used (Residual Neural Network ResNet-50 architecture).…”
mentioning
confidence: 99%